Topological insulators within the family of Heusler materials - Chadov, Stanislav; Felser, Claudia (Springer Verlag, 2016)
The first system, in which the quantized spin Hall effect has been demonstrated experimentally, was the zinc-blende binary HgTe semimetal. The aim of our contribution is to show that, by having the similar crystal structure but ternary chemical composition, Heusler compounds naturally represent much more diverse family of nontrivial semimetals, compared to the binaries. Here we will give an overview of these topologically nontrivial systems, by discussing the role of the spin-orbit coupling for the band inversion and the crystal symmetry mechanisms which lead to the semimetallic zero-gap state in these materials.
CRIS-Team Scopus Importer:2023-03-20